Factors that influence the purchase intensity of pirated products (CDs/DVDs) / Noranisha Jamaludin and Nur Farah Suhaimi - Jamaludin, Noranisha; Suhaimi, Nur Farah (Faculty of Business and Management, 2013)
This research paper is a partial requirement for the fulfilment of BBA (Hons) Marketing which the title of the research is “FACTOR THAT INFLUENCE THE PURCHASEINTENSITY”. The objective of the study conducted is to determine the important factor that influence purchase intensity of the pirated products (CDs/DVDs) and to suggest appropriate actions that should be taken to overcome the pirated problem in future. This study was conducted at Selangor which will specifically location are around Cyberjaya, Putrajaya, Puchong, Seri Kembangan and Bangi area. In this study, 150 sets of questionnaires had been distributed and it shown a good feedback when we received back 150 sets of questionnaires fulfil with answer. All data and information gathered through questionnaire were considered as primary data this research is fully based on questionnaire. The questionnaire design based on the theoretical framework in this study. This included five sections Section A (1) related to dependent variable which is price intensity and meanwhile Section A (2), A (3), and A (4) consist of independent variables questions which is price, trust, satisfaction and quality while section B consists of respondent profile. The researcher analyse the data by using SPSS 21 in order to identify the mean, median, standard deviation, reliability test, correlation testing and regression analysis. Based on the result, it’s revealed that there are three hypotheses that are supported which are price, trust and satisfaction.